Spectrophotometric analysis of sapstain caused by Botryodiplodia theobromae, aureobasidium pullulans and Aspergillus niger on three rubberwood clones - Ashari A J; Palfreyman J W; Wong A H H (Journal of Tropical Forest Products, 2000)
Rubberwood (Hevea brasiliensis) blocks from three clones (GT 1 and PB 217 from Bukit Pilah Estate, Negeri Sembilan, and RRIM600 from Tangkah Estata, Johor in Peninsular Malaysia) were inoculated with the test fungi and incubated for four weeks, after which they were air dried and sanded (about 0.5 mm), and then quantitatively assesed for sapstain spectrophotometry. Blue stain from B. theobromae was still present and pronounced after sanding, and was darker (absorbance: 56.5;) compared with wood infected by Aspergillus niger (38.2;) or Aureobasidium pullulans (35.9;). Clone RRIM600 had higher darkness (41.9;) compared with clone PB217 (38.5;). The mean per cent darkness of clone GT 1 (39.7;) was not different from clones RRIM 600 and PB217. Single or mixed inocula of A. pullulans and Aspergillus niger effectively controlled B. theobromae infection in wood of clones RRIM 600 and PB 217, thus suggesting a potential for biocontrol of sapstain in rubberwood.
Source Year: 2002
Keywords: Aureobasidium pullulans and Aspergillus niger; Botryodiplodia theobromae; Rubberwood clones